Global warming, the atmospheric brown cloud, and the changing Indian summer monsoon. (July 2015) - Liepert, Beate G.; Giannini, Alessandra
Much scientific discussion has focused on rising greenhouse gas emissions and changing rainfall patterns in an increasingly warmer world. In fact, preventing the worst impacts of climate change on future human well-being will mean dealing with heightened flood and drought risks. The authors explain why the complex science of the shifting rainfall patterns and intensities caused by global warming is made even more complex by increasingly extreme air pollution. The article describes how scientists now think that the so-called "atmospheric brown cloud" over India affects the summer monsoon more than global warming does. In India, agriculture, industrial productivity, and life in general depend on monsoonal downpours that bring huge amounts of water to the subcontinent, feeding rivers and aquifers and cooling the land between June and September. As bad as it sounds, the scenario in which air pollution plays a major role in climate is actually good news for developing nations such as India. Pollution control is a regional and local problem that developing nations need to address in any case because of the huge human health costs related to it. The authors also warn that once pollution is brought under control, the full extent of global warming caused by developed nations' greenhouse gas emissions from decades ago will become more prevalent and its impacts on the Indian monsoon will be unmasked.